What to expect when using globular clusters as tracers of the total mass distribution in Milky Way-mass galaxies - Hughes, Meghan E.; Jethwa, Prashin; Hilker, Michael; van de Ven, Glenn; Martig, Marie; Pfeffer, Joel L; Bastian, Nate; Kruijssen, Diederik; Trujillo-Gomez, Sebastian; Reina-Campos, Marta; Crain, Robert A (Monthly notices of the Royal Astronomical Society, 2021)
Dynamical models allow us to connect the motion of a set of tracers to the underlying gravitational potential, and thus to the total (luminous and dark) matter distribution. They are particularly useful for understanding the mass and spatial distribution of dark matter (DM) in a galaxy. Globular clusters (GCs) are an ideal tracer population in dynamical models, since they are bright and can be found far out into the halo of galaxies. We aim to test how well Jeans-Anisotropic-MGE (JAM) models using GCs (positions and line-of-sight velocities) as tracers can constrain the mass and radial distribution of DM haloes. For this, we use the E-MOSAICS suite of 25 zoom-in simulations of L* galaxies. We find that the DM halo properties are reasonably well recovered by the JAM models. There is, however, a strong correlation between how well we recover the mass and the radial distribution of the DM and the number of GCs in the galaxy: the constraints get exponentially worse with fewer GCs, and at least 150 GCs are needed in order to guarantee that the JAM model will perform well. We find that while the data quality (uncertainty on the radial velocities) can be important, the number of GCs is the dominant factor in terms of the accuracy and precision of the measurements. This work shows promising results for these models to be used in extragalactic systems with a sample of more than 150 GCs.